Osteocytes: master orchestrators of skeletal homeostasis, remodeling, and osteoporosis pathogenesis - Wu, Yan; Gan, Donghao; Liu, Zhikang; Qiu, Daodi; Tan, Guoqing; Xu, Zhanwang; Xue, Haipeng (Frontiers in Cell and Developmental Biology, 2025)
The skeleton functions as an endocrine organ. Osteocytes maintenance of skeletal strength and energy balance by sensing mechanical stress and communicating with surrounding cells. They are currently considered key regulators of bone remodeling, mineral metabolism, and systemic homeostasis. Osteocytes originate from osteoblasts and are embedded in the lacunar-tubular network. They express proteins such as DMP1, sclerostin, and FGF23, and influence Wnt signaling, the RANKL/OPG axis, and phosphate metabolism. We review the latest studies in the field of osteocyte biology, focusing on their mechanotransduction through Piezo1 and integrins, regulation of osteoclastogenesis and osteogenesis, and their interactions with the bone marrow microenvironment, including immune and vascular cells. In osteoporosis, osteocyte dysfunction is manifested by apoptosis, ferroptosis, and pyroptosis. These changes, together with altered secretion, lead to uncoupled remodeling, disruption of the lacuno-canalicular network and metabolic imbalances that are intertwined with inflammation and bone marrow fat deposition. Osteocytes play an important role in fracture healing and adaptive remodeling under mechanical stimulation, promoting angiogenesis and stem cell recruitment. A growing number of emerging approaches, including stem cell therapy, CRISPR editing, and AI-driven multi-omics for precision medicine, are accelerating osteocyte-related research and the development of therapeutic strategies. These studies reveal the clinical potential of osteocyte-targeted therapies to prevent osteoporosis, improve bone strength, and enhance regeneration. By integrating molecular, cellular, and systems knowledge, we highlight osteocytes as a key therapeutic target to combat bone diseases and promote bone regeneration.